COMPARATIVE ANALYSIS OF ADVERBS IN ENGLISH AND UZBEK LANGUAGES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article is devoted to a comparative analysis of the structural, semantic, and functional characteristics of adverbs in English and Uzbek languages. The study examines the types of adverbs, their formation methods, their position in sentences, and their semantic features. The aim is to identify similar and different aspects of adverbs in English and Uzbek languages, evaluate their communicative functions, and highlight problems that arise during translation. Based on examples from various sources, the linguistic and sociolinguistic characteristics of adverbs in these languages are analyzed.